EFEKTIFITAS KOAGULAN PAC DAN HCA PADA APLIKASI UNIT HIDROULIC KOAGULASI DALAM PENYISIHAN TSS AIR PERMUKAAN - Firra Rosariawari; Aulia Ulfah Faradiba (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Surface water is needed as raw water to meet water quality requirements. This study applies a coagulation unit with a hydroulic process, flocculation and sediemntation. The three units are designed in a simple, energy efficient and portable circuit. This unit can be used to treat surface water with portable scale. The discharge of 9 L / minute as an inlet is expected to be sufficient to meet the needs of clean water on a household. PAC and HCA coagulants were used to remove turbidity and suspended solids with various concentrations. The test parameter used to measure the effectiveness of this unit in removing suspended solids is TSS. TSS removal is very significant with the addition of a filtration unit.